Comparative Study of Sensory Attributes of Leafy Green Vegetables Grown Under Organic and Conventional Management - Kripa Dhakal; Ramasamy Ravi; Dilip Nandwani (International Journal on Food, Agriculture and Natural Resources, 2021)
This study was carried out to compare the sensory qualities of leafy green vegetables (collard, kale, lettuce and swiss chard) grown under organic and conventional production systems. Four leafy greens were produced on an organically and conventionally managed research farm of Tennessee State University, Nashville, TN in Spring 2019 and 2020. Crops in a conventional field were grown in the open field, whereas in organic field crops were grown in the open and under three different row covers (agribon cloth, insect net and plastic). Row covers in organic systems were used to protect crops from insect damage. Plant samples were collected from all the treatments and evaluated for sensory qualities including color, texture, taste, odor and flavor following two approaches i.e., instrumental and via consumer panel perception. Consumer panel perception results showed minor differences in the sensory qualities between organic and inorganically produced leafy greens. Instrumental methods showed no differences in color parameters of kale, lettuce and swiss chard grown under organic and conventional production systems. In collard, the lightness (L*), b* (yellow-blue axis), brightness (Y) and chroma (C) values were higher in conventional, while hue angle was higher in organic (open). There were no differences in instrumental textural values of organically and conventionally grown leafy greens. Among row covers, the textural value of collard and kale was higher in open relative to row covers. The content of main quality contributors 1-Hexanol was higher in conventionally grown collard compared to organic (open). Aldehyde compound was higher in organically grown kale and trans-hex-2-enyl-acetate (Ester) compound was higher in conventionally grown kale. Monoterpenes were higher in organic lettuce and ketones were higher in conventionally grown lettuce. Overall, there were not many differences in the sensory qualities of leafy greens grown under organic and conventional production systems. Further comparative studies between organic and conventional systems on sensory qualities of leafy greens are needed.